California Host Building, Golden Gate International Exposition, San Francisco (H.S. Crocker Co., Inc.)
The circular Court of Seals, with slender golden columns, separates the buildings of the State of California and San Francisco at the Golden Gate International Exposition on Treasure Island in San Francisco Bay. Foreground, a Siamese lighting standard